Pathophysiological Pathways Linking Diabetes to Cardiac Hypertrophy: From Insulin Resistance to Personalised Cardioprotection - Joshi, Gaurav; Goutam, NIshant; Shivani, Shivani; Kaushal, Kanika; Sharma, Abhishashi; Kaur, Harmanbir; Joshi, Neeraj (Scripta Medica, 2026)
Diabetes and cardiac hypertrophy are closely interconnected, sharing overlapping metabolic and cardiovascular pathways. This review aimed to investigate the underlying mechanisms that drive this relationship and to evaluate current diagnostic and therapeutic strategies with the goal of improving clinical outcomes. An extensive review of recent literature was undertaken to explore how factors such as insulin resistance, hyperglycaemia, inflammation, oxidative stress and lipotoxicity contribute to cardiac remodelling and functional decline. Developments in diagnostic modalities, including advanced imaging techniques and emerging biomarkers, were examined alongside both lifestyle interventions and pharmacological treatments. Diabetes is a significant contributor to the progression of cardiac hypertrophy, primarily through metabolic dysregulation and persistent low-grade inflammation. The importance of early detection—using sophisticated imaging tools and biomarker profiling—has become increasingly evident for timely and effective intervention. Therapeutic agents such as metformin, sodium glucose cotransporter-2 inhibitors (SGLT2) and glucagon like peptide-1 receptor agonist (GLP-1) have demonstrated beneficial effects in reducing cardiovascular complications in individuals with diabetes. Moreover, novel approaches, including chronotherapy and personalised medicine, are gaining traction as potential means to enhance treatment efficacy and patient outcomes. The robust association between diabetes and cardiac hypertrophy underscores the necessity for a more integrated and nuanced approach to diagnosis and management. Combining early detection with targeted pharmacotherapy and personalised care strategies offers a promising route to addressing this complex clinical challenge. Continued research is essential to refine these approaches and to optimise long-term outcomes for affected patients.
Keywords: Diabetes mellitus; Cardiac hypertrophy; Lipotoxicity; Pharmacology, chrono; Sodium-glucose transporter 2 inhibitors